Development of the multi-project forming method in shipping company’s development - Prykhno, Yuliya (Technology audit and production reserves, 2017)
The object of research is the processes of shipping company’s multi-project content managing. The subject of the study is the method of multi-project management of the development of shipping companies. One of the most problematic places is the formation of a strategy for the development of a shipping enterprise. The strategy of a shipping company involves setting long-term goals of the company, identifying resources for their achievement and technology development strategy. It is proved that the formation of a competitive shipping strategy for a shipping company is a rather complex and lengthy process. The purpose of this process is the choice of development projects that will enhance the company’s long-term business performance. During the study, methods of system analysis were used, which allowed to determine that: in conditions of fierce competition and dynamic environment, shipping companies operate in a number of areas; there is a need to plan a large number of parallel projects and rational use of company resources. The method of optimizing of the multi-projects’ content is obtained. It allows forming a multi-enterprise development project, taking into account not only the constraints on resources, but also the conformity of the results of the multi-project to the strategic goals. The point is that proposed method has a number of features, namely: the two-tier nature of planning and management: at the level of individual projects and at the level of strategy in general; structuring of the strategic planning process in the distribution of resources, time, profit; development of the potential of the shipping company. It provides the opportunity for rational allocation of company resources. Compared to similar well-known methods, it provides the following benefits: achieving all strategic goals, linking strategy to development projects, optimal allocation of resources.